The Distinction Between the Initial Two Commandments: An Exegetical Study of Exodus 20:2-6 - Blasius Abin; Edwin M. Lumingkewas; Budi Harwanto (International Journal of Education, Information Technology, and Others, 2023)
The dissimilarity between the initial two commandments within God's law (Exodus 20:3-6) serves to affirm the theological principles presented in the Bible. This research paper employs fundamental methodologies, such as analysing the textual structure and literal context of the studied passage. Its primary objective is to investigate the disparity between the two commandments and explore their significance within Christian theology. After a meticulous examination of the syntax and contextual connections, this paper draws three conclusions. Firstly, the initial two commandments pertain to two distinct facets of biblical theology. The first commandment emphasizes the worship of the Lord as the primary subject, while the second commandment focuses on the proper way to worship Him. Secondly, the purpose of the first commandment is to protect Israel against external threats, particularly the worship of "other gods.” Thirdly, the second commandment aims to safeguard Israel against internal threats, manifested using images as objects of worship. The utilization of images has the potential to undermine the covenant relationship between God and Israel. In summary, the worship of gods other than Yahweh and the incorporation of images in worship are two separate laws with crucial disparities. These differences hold great significance in Christian theology, as they anticipate the presence of modern idolatry and various attempts to materialize the worship system